Integration Of Digital Campaigns, Experiential Events, And Brand Support In Raising Awareness Of Early Detection Of Breast Cancer - Aji, Imanuel Deny Krisna; Nathania, Jovita (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study aims to analyze the influence of digital campaigns, events, and brand support on awareness of early detection of breast cancer in the social movement "Not Just October" (NCO). The research used a quantitative approach with a survey method on 100 respondents who were exposed to the campaign. Data were collected through a Likert scale-based questionnaire and analyzed using multiple linear regression. The results of the study showed that digital campaigns, events, and brand support had a significant influence on awareness of early detection of breast cancer, while the remainder is influenced by other factors outside the model. These findings indicate that an integrated communication strategy through digital media, direct experiences, and brand collaborations is effective in increasing public health awareness, although the level of awareness generated is still in the moderate category. Theoretically, this research strengthens the concept of social marketing communication and experiential communication in the context of health campaigns. Practically, this study recommends strengthening the integration of communication channels and increasing the intensity of campaigns to encourage more sustainable changes in early detection behavior.